Strategi Peningkatan Kualitas Pelayanan Administrasi Umum di Kelurahan Pasirjati Kecamatan Ujungberung Kota Bandung - Sari Pitriyanti; Joni Dawud; Sait Abdullah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The purpose of this study was to determine the general administration services in Pasirjati Village based on the community satisfaction index and the Electronic Community Satisfaction of the Bandung City Government. In an effort to improve the quality of public administration services, a strategy based on internal and external environmental analysis is needed as a reference. This study uses a descriptive analytic qualitative approach. (Fred David:2015) used the right strategy formulation through an approach with the stages of analyzing the IFE and EFE matrices, the IFE and EFE quadrants, and the Quantitative Strategic Planning Matrix (QSPM). From the results of the IFE-EFE rating and weight analysis, SWOT quadrant, SWOT matrix and Quantitative Strategy Planning Matrix (QSPM) that have been carried out, the results of the strategy carried out are Aggressive Strategies (SO) to improve the quality of public administration services in Pasirjati Village, namely expanding access to service distribution and mobile services.